Decomposition of K-feldspar by potassium hydroxide solution in the hydrothermal system. (15th March 2022) - Wu, Yusheng; Li, laishi; Liu, Xiaofu; Wang, Yuzheng; Li, Mingchun
Graphical abstract: Highlights: A hydrothermal alkaline combined with ammonium hydrogen sulfate solution leaching process was developed to utilize comprehensively K-feldspar. The transformation of K-feldspar in hydrothermal process is as follow: Microcline → kaliophilite (as metastable materials) → kalsilite. The K-feldspar is completely decomposed at 280 ℃ for 120 min. Potassium and aluminum in kalsilite are easily leached by ammonium hydrogen sulfate solution. Abstract: A novel hydrothermal alkaline process combined with ammonium hydrogen sulfate solution leaching process for improving the comprehensive utilization value of the mineral K-feldspar was developed. In this technology, K-feldspar was first decomposed by the alkaline hydrothermal method, forming kalsilite in the resultant products, where potassium and aluminum were easily leached by ammonium hydrogen sulfate solution. The effects of hydrothermal temperature, concentration, and excess rate of potassium hydroxide on the leaching rate of alumina were investigated. The products obtained under various conditions were characterized by X-ray diffraction (XRD), scanning electron microscope (SEM), X-ray fluorescence (XRF) and Fourier transform infrared spectroscopy (FTIR). The results show that the hydrothermal temperature has a predominant influence on the hydrothermal decomposition of K-feldspar. With the hydrothermal time of 30 min, the leaching rate of alumina at 280 °C is 62.5 % higher than that at 220 °C. The K-feldspar is completely decomposed at 280 °C for 120 min. The concentration of potassium hydroxide has little effect on the decomposition of K-feldspar. The transformation of K-feldspar in the proposed hydrothermal process is as follows: Microcline → kaliophilite (as metastable materials) → kalsilite.